Gestational weight gain and body composition of full-term newborns and infants: a cohort study - Sylvia R. Nehab; Letícia D. Villela; Fernanda V. M. Soares; Andrea D. Abranches; Daniele M. R. Araújo; Leila M. L. da Silva; Yasmin N. V. Amaral; Saint Clair G. Junior; Maria Dalva B. B. Meio; Maria Elisabeth Moreira (BMC, 2020)
Abstract Background The association between gestational weight gain and neonatal body composition has been inconsistent, exposing the need for further research. The aim of this study was to evaluate whether gestational weight gain influences the body composition of full-term newborns and infants up to 4 months old. Methods A cohort study was performed with 124 participants divided into categories of gestational weight gain according to the 2009 Institute of Medicine guidelines. The anthropometric and body composition data of newborns and infants acquired using air displacement plethysmography (PeaPod®) were collected at 96 h, 1 month, 2 months and 4 months of life. In the statistical analysis, the chi-square test was used to analyze categorical variables, and ANOVA was used to analyze numerical variables. Univariate analysis was performed, and the absolute and relative frequencies of the categorical variables, as well as mean and standard deviation of the numerical variables, were obtained. Bivariate analysis was performed for the categories of gestational weight gain and gestational and neonatal characteristics. When adjustments to gestational hypertension, gestational diabetes, and pregestational body mass index (BMI) were analyzed by linear regression, gestational weight gain remained a significant variable for newborn percent fat mass. For all analyses, a significance level of 5% was adopted. Results Gestational weight gain was adequate in 33.8% of the participants, excessive in 41.1% and insufficient in 25%. Women with excessive weight gain had higher pregestational BMIs and a higher incidence of gestational hypertension. Their newborns had a higher body mass, body fat mass in grams and percent fat mass than the infants born to mothers with adequate or insufficient gestational weight gain. No significant differences were observed in body composition at 1, 2 and 4 months of life during infant follow-up. Conclusion Excessive gestational weight gain may alter the body composition of newborns at birth. Further studies are required to better evaluate infant follow-up. Trial registration Clinical Trial Registry: NCT00875251 on April 3, 2009.